Multilevel impacts of a pediatric early warning system in resource-limited pediatric oncology hospitals - Mirochnick, Emily; Graetz, Dylan E.; Ferrara, Gia; Puerto-Torres, Maria; Gillipelli, Srinithya R.; Elish, Paul; Muniz-Talavera, Hilmarie; Gonzalez-Ruiz, Alejandra; Armenta, Miriam; Barra, Camila; Diaz-Coronado, Rosdali; Hernandez, Cinthia; et al. (Frontiers in Oncology, 2022)
Background: Pediatric Early Warning Systems (PEWS) reduce clinical deterioration, improve interdisciplinary communication, and provide cost savings; however, little is known about how these impacts are achieved or related. This study evaluates the multi-level impacts of PEWS in resource-limited pediatric oncology centers. Methods: We conducted 71 semi-structured interviews including physicians (45%), nurses (45%), and administrators (10%) from 5 resource-limited pediatric oncology centers in 4 Latin American countries. Interviews were conducted in Spanish, transcribed, and translated into English. A code book was developed using a priori and inductively derived codes. Transcripts were independently coded by 2 coders, achieving a kappa of 0.8-0.9. Thematic content analysis explored perceived impacts of PEWS at the level of the patient, clinician, healthcare team, and institution. Results: PEWS improved the quality of attention for patients, reducing morbidity and mortality. Clinicians felt more knowledgeable, confident, and empowered providing patient care, resulting in greater job satisfaction. PEWS affected team dynamics by improving interdisciplinary (ward and intensive care unit) and interprofessional (physicians and nurses) relationships and communication. This ultimately led to institutional culture change with emphasis on patient safety, collaboration with other centers, and receipt of institutional awards. Together, these impacts led to hospital-wide support of ongoing PEWS use. Conclusions: In resource-limited hospitals, PEWS use results in multi-level positive impacts on patients, clinicians, teams, and institutions, creating a feedback loop that further supports ongoing PEWS use. These findings can guide advocacy for PEWS to various stakeholders, improve PEWS effectiveness, and inform assessment of other interventions to improve childhood cancer outcomes.